PRELIMINARY DATA ON THE PINETO GABBROIC MASSIF AND NEBBIO BASALTS: PROGRESS TOWARD THE GEOCHEMICAL CHARACTERIZATION OF ALPINE CORSICA OPHIOLITES - Saccani, Emilio; Padoa, Elisa; Tassinari, Renzo (Ofioliti, 2000)
The Pineto Massif and Nebbio ophiolitic sequences represent two main examples of Corsican ophiolites that, similarly to the well-known Balagne Nappe, have not undergone high pressure-low temperature alpine metamorphism. For this reason these sequences have been so far referred to the Balagne-type ophiolites. The Pineto Massif is composed of a cumulitic intrusive sequence consisting of layered troctolites, dunites, gabbros, and anorthosites cross cut by basaltic dykes. The chemical composition of both cumulates and dykes reveal an oceanic tholeiitic affinity. In particular, the Pineto Massif basaltic dykes have REE patterns similar to those of N-MORBs with slight LREE/HREE depletion, as also evidenced by low CeN/YbN (0.9-1.2) ratios. The Nebbio ophiolitic sequence consists of pillow and massive lava flow basalts capped by cherts, Calpionella limestones, and Cretaceous siliciclastic formations. Chemically, the Nebbio basalts are similar to ocean-floor basalts. They are characterized by LREE enrichment with respect to HREE, as evidenced by the CeN/YbN (1.2-1.9) ratios. Their REE patterns are similar to those shown by T-MORBs. Geochemical data show that the Pineto Massif ophiolites are different from the Balagne Nappe T-MOR basalts, suggesting that any correlation between the Pineto Massif ophiolites and the Balagne Nappe should be ruled out. By contrast, they highlight close analogies between the Pineto Massif and the Internal Ligurides ophiolites from the Northern Apennine, suggesting that both these ophiolites represent fragments of the Piedmont-Ligurian oceanic lithosphere located in an internal oceanic position, relatively far from the continental margins. Conversely, the Nebbio basalts show striking geochemical similarities to those of the Balagne, further supporting the hypothesis that both the Balagne and Nebbio ophiolites could represent fragments of oceanic crust generated in the early stages of the Piedmont-Ligurian basin oceanization.